2020
DOI: 10.1016/j.scitotenv.2020.139298
|View full text |Cite
|
Sign up to set email alerts
|

Early SARS-CoV-2 outbreak detection by sewage-based epidemiology

Abstract: Detect early presence of virus in sewage.• SARS-CoV-2 has been isolated from the faeces.• Sampling, preserving and processing samples are critical issues.• Consider a SARS-CoV-2 sewage-monitoring plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 9 publications
5
114
0
2
Order By: Relevance
“…This approach can provide rapid and reliable information about the disease outbreaks and their trends in the population. It seems to be suitable for surveillance of mild, subclinical, or asymptomatic cases [25,[40][41][42][43][44]. Our preliminary results confirmed the potential of this approach for use as an early warning tool for effective surveillance of the diseases spread.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This approach can provide rapid and reliable information about the disease outbreaks and their trends in the population. It seems to be suitable for surveillance of mild, subclinical, or asymptomatic cases [25,[40][41][42][43][44]. Our preliminary results confirmed the potential of this approach for use as an early warning tool for effective surveillance of the diseases spread.…”
Section: Discussionsupporting
confidence: 71%
“…Wastewater monitoring has been successfully used for tracking drug consumption, pharmaceutical use, water pollution, and antibiotic resistance [36][37][38]. However, through SARS-CoV-2 detection in wastewater, it is also possible to obtain unique epidemiological information on its occurrence in the population (presence, absence, and trends: increase, stagnation, decrease) [39][40][41][42][43][44]. A properly set up wastewater monitoring system enables outbreak monitoring and trend observations in the numbers of viral diseases of future periods and may be used as an early warning tool to set up a system for effective surveillance of disease spread.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of COVID-19 in the tested population is not always known, which could affect the optimal pool size. This could be addressed either by external estimates, such as a previous run of individual samples, rate of symptomatic patients, or alternative methods such as serological screening or wastewater titres monitoring [28,29]. Alternatively, it is possible to dynamically adapt pooling sizes, when the measured rate of positive samples is different than expected.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Australia ( Ahmed et al, 2020 ) showed that the number of infected individuals in the catchment areas could be reasonably estimated by detecting the copy numbers of SARS-CoV-2 RNA in the wastewater, which verified that early detection of coronavirus in wastewater might be a viable surveillance strategy for COVID-19 infections ( Daughton, 2020 ; Orive et al, 2020 ; Wu et al, 2020b ) as previously demonstrated for hepatitis A virus, norovirus ( Hellmér et al, 2014 ) and poliovirus ( Asghar et al, 2014 ; Lodder et al, 2012 ). Although there was no sufficient evidence that fecal-oral transmission of COVID-19 was viable, while there was evidence showed that SARS-CoV-2 could be easily and sustainably transmitted in the community in Shenzhen, China, because the proportion of COVID-19 patients without definite exposure from January 25 through February 5 (11%) was much higher than that before January 24 (6%) ( Liu et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%